DEMATEL-AHP multi-criteria decision making model for the selection and evaluation of criteria for selecting an aircraft for the protection of air traffic - Petrović, Ivan; Kankaraš, Milan (Decision Making: Applications in Management and Engineering, 2018)
This paper describes an approach in the selection and evaluation of the criteria and attributes of criteria for selecting the air traffic protection aircraft. After collected initial criteria and attributes, the interaction between criteria and attributes of criteria for the selection of the aircraft especially for the protection of air traffic was evaluated by 45 respondents. Data processing and criteria and attributes selection were carried out by the DEMATEL method (by eliminating less significant criteria and attributes). Furthermore, the weight values of each criterion and attribute were determined by the AHP method. Prioritization was carried out using an eigenvector method. For determination reliability the consistency ratio was checked for each result. As a result the model for the selection of the aircraft was proposed.